Zero Trust for SQL Server: A Three-Layer Security Architecture - Capil, Maynard; Dasig Jr., Daniel (JPAIR Multidisciplinary Research, 2026)
Enterprise database systems are frequently targeted due to their reliance on perimeter-based, static access control models that lack continuous verification and privilege minimization. This study designed and empirically validated a three-layer Zero Trust architecture for Microsoft SQL Server that natively integrates instance-level authentication governance, enhanced Role-Based Access Control (RBAC) with Row-Level Security (RLS) and Just-in-Time (JIT) privilege elevation, and metadata-driven Attribute-Based Access Control (ABAC) through data classification — all without requiring external security middleware. Employing design science and applied experimental methodology, architecture was deployed in a live production environment comprising 589 databases and 132 identities over a 90-day post-implementation period. Chi-square tests of independence with Cramér’s V effect size confirmed statistically significant reductions: login misuse declined by 82.1%, malicious authentication attempts by 66.7%, deployment errors by 59.8%, and reporting disruptions by 43.7%. Overprivileged accounts decreased by 84.2%. These results demonstrate that a coordinated, database native Zero Trust pipeline substantially reduces attack surfaces and insider risk in enterprise SQL Server environments. The proposed architecture aligns with globally recognized compliance frameworks, including ISO/IEC 27001 and GDPR, offering a replicable and regulatory-ready deployment model for enterprise environments across diverse jurisdictions.